Programa Ciência sem Fronteiras no contexto da política de internacionalização da educação superior brasileira - Martins, Joira Aparecida Leite de Oliveira Amorim (2015)
This Master’s thesis is about the Science without Borders Program (CsF), a program created by the Brazilian Federal Government to “consolidate, expand and internationalize Brazilian science, technology, innovation and competitiveness by means of interchange and international mobility” (BRAZIL, 2014). The objective of this research is to analyze the conception and implementation of CsF within the internationalizing policies of Brazilian higher education. This is an exploratory qualitative study, using semi-structured interviews of 3 representatives of the institutions that created and now manage CsF. Data analysis focuses on CsF idealization, creation, objectives, foments and adaptations, according to the perspective of internationalizing policies of higher education. The following categories were analyzed, through the lens of the dialectical method: conception, encompassing idealization and creation; and implementation, encompassing characteristics and perspectives. The research shows that the internationalizing policies of higher education in Brazil, according to data from CsF, tend to neglect mutual solidarity so as to reinforce the current political and economical model.